DIGITAL TWIN ACCOUNTING REAL-TIME SIMULATION OF COMPANY BALANCE SHEET IN THE BUSINESS METAVERSE - Ilham Maulana (Jurnal Penelitian Progresif, 2025)
With the advancement of metaverse technology and the need for real-time financial data, theaccounting sector is undergoing rapid digital transformation. An innovative solution to improve theaccuracy, transparency, and efficiency of corporate financial reporting is the digital twin, a virtualreplica of a physical system. developed an accounting digital twin system to model a company'sbalance sheet in real-time in the business metaverse world and assess its effectiveness and efficiency.This study employed a research methodology and a systems development approach. Requirementsanalysis, architectural design, implementation, testing, and validation were the necessary steps todevelop the system. Data were collected through direct observation, stakeholder interviews, literatureresearch, and system testing on 15,000 transactions during a simulation period. Validation wasconducted by fifty business stakeholders and twenty accounting experts. With an accuracy rate of 99.2% and an average response time of 1.8 seconds, the accounting digital twin method successfullycreated a virtual replica of the company's balance sheet. The system had an uptime of 99.7 % and wascapable of processing up to 850 transactions per minute. 3D visualization in the metaverse achieved auser engagement rate of 91%. Simulation results showed a 78% reduction in reporting time, a 38%reduction in operational costs, and a 42% increase in data accuracy. Furthermore, the systemsuccessfully provided early warnings 72 hours before a liquidity crisis. Validation demonstrated a 96.7% technical integration success rate and a 93% user satisfaction rate. In a real-time company balancesheet simulation in the business metaverse, the digital accounting twin was proven to improve thequality of financial information, accelerate the decision-making process, and enhance corporateaccountability and transparency. This system helps the contemporary accounting sector transform intoa digital one. This research contributes to the development of accounting information systems,business digital transformation, and financial technology innovation. The results can be used as areference for companies wishing to implement digital twin technology in their accounting practices.